2010
DOI: 10.1088/1367-2630/12/3/033013
|View full text |Cite
|
Sign up to set email alerts
|

Multiple condensed phases in attractively interacting Bose systems

Abstract: We investigate a Bose gas with finite-range interaction using a scheme to eliminate unphysical processes in the T-matrix approximation. In this way the corrected T-matrix becomes suitable to calculate properties below the critical temperature. For attractive interaction, an Evans-Rashid transition occurs between a quasi-ideal Bose gas and a BCS-like phase with a gaped dispersion. The gap decreases with increasing density and vanishes at a critical density where the single-particle dispersion becomes linear for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…We use a scheme to eliminate self-interaction in the T-matrix approximation, to calculate properties below the critical temperature [25][26][27][28] . The Green function 29,30 for particles with momentum q and Matsubara frequency…”
Section: A Condensed Phasementioning
confidence: 99%
“…We use a scheme to eliminate self-interaction in the T-matrix approximation, to calculate properties below the critical temperature [25][26][27][28] . The Green function 29,30 for particles with momentum q and Matsubara frequency…”
Section: A Condensed Phasementioning
confidence: 99%
“…[7] it was found that both of these phases are unstable against mechanical collapse; that is, the bosons with an attractive interaction tend to form clusters of particles. Moreover, an extension of the mean-field results given in [7,18,19] by the leading-order fluctuation contributions [20,21] or even higher-order corrections [22] to the thermodynamic potential does not lead to a stable homogeneous phase of bosons with the pairing potential. It was observed in [23] that by confining bosons with pairing interactions in a trap, which produces a gap between the ground and the excited states, one can protect the system from the mechanical instability.…”
Section: Introductionmentioning
confidence: 94%
“…The advantage of eliminating only the contributions of single channels as proposed in Refs.[4] and [5] is that the formation of pairs and their condensation can be described within the same approximation. This has also resulted in the description of different phases in interacting Bose systems [7].On the other hand there exist a well established theory to describe systems with condensates in terms of anoma-lous functions, for review see [8]. Let us consider bosonic particles which can form a condensate either bosons or paired fermions.…”
mentioning
confidence: 99%
“…[4] and [5] is that the formation of pairs and their condensation can be described within the same approximation. This has also resulted in the description of different phases in interacting Bose systems [7].…”
mentioning
confidence: 99%